Justifying enterprise resource planning (ERP) investment: A case study using technology, organization, and environment (TOE) framework - Rahman, Arief; Ratnawati, Yeni (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2021)
The aim of this study is to analyze the implementation of Enterprise Resource Planning (ERP) in the context of Technology, Organization and Environment (TOE). This current research uses case study approach in a company in Yogyakarta. Researchers used qualitative method by involving 31 informants in semi-structured interviews. The informants were management of a company in various level of positions. They are relevant key persons in the implementation of ERP systems, and the users of the ERP systems. Data analysis techniques included data collection, coding and reduction of data, and discussion and summarizing, were implemented. To examine validation of research data, this research used source triangulation. Results of the study show that there were challenges or obstacles and benefits of ERP systems implementation related to technology, organization and environment. The results are further discussed in this paper, including the implications for companies and literature. This research contributes by providing empirical evidence and examining TOE approach in the same time in the context of ERP implementation.